A Simulated Annealing Approach for the Joint Order Batching and Order Picker Routing Problem with Weight Restrictions - Grosse, Eric; Glock, Christoph; Ballester Ripoll, Rafael (IJOQM, 2014)
This paper studies the joint order batching and order picker routing problem in conventional multi parallel-aisle picker-to-part order picking systems. It complements prior publications by considering capacity constraint that is formulated as a function of total item weight, instead of item count. A mathematical model is formulated and a simulated annealing algorithm is developed to batch orders and to determine pick tours. The intention of the paper is to provide a more realistic model and to improve classical batching and routing heuristics. It thereby pays special attention to the practical applicability of the model. The proposed methods are compared and evaluated in an extensive numerical study, and it is shown that the developed approach leads to an improved solution for the joint order batching and order picker routing problem, as compared to classical heuristics for this problem.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.03 Estudios industriales; ODS 9 - Industria, innovación e infraestructura; ODS 12 - Producción y consumo responsables; Order Picking; Order Batching; Warehouse; Simulated Annealing; Picker-to-Part System